Eat cake. Be brave - Radke, Melissa (New York : Grand Central Publishing, 2018)
The popular online video personality shares an empowering collection of essays about her midlife decision to be brave, change her life, and regain her sense of self-worth.
Keywords: Radke, Melissa -- Anecdotes; Self-esteem in women; Self-confidence.; Women -- Psychology; Courage; Self-esteem in women -- Humor; Self-confidence -- Humor; Women -- Psychology -- Humor; Courage -- Humor; Self-reliance.; Women -- Psychology; Estime de soi chez la femme; Confiance en soi; Femmes -- Psychologie; Courage; Estime de soi chez la femme -- Humour; Confiance en soi -- Humour; Femmes -- Psychologie -- Humour; Courage -- Humour; Nonfiction; essays; humor; Anecdotes; Essays; Humor; Anecdotes; Essais; Humour